Analysis of Issues, Potential, and Future Development Direction of Retail Cash Waqf-Linked Sukuk - Umam, Khoirul; Muzaki, Rofi; Afif, Mufti; Nurfattah, Arizqiya (AIBPM Publisher, 2024)
Hence, the objective of this study is to analyze the potential and challenges surrounding the development of Retail CWLS in order to ascertain a favorable direction for its sustained growth. This study examines the challenges encountered in the development of Retail CWLS products. These include a decline in wakif interest for money waqf in Retail CWLS which occurred during the Covid-19 pandemic outbreak, the government has not been consistent in determining Retail CWLS yield coupons, the risk of loss in the form of loss of waqf assets, low literacy regarding Retail CWLS among The Younger Generation in Indonesia. The potential CWLS in the form of high interest among generation X and Millennial people, the maximum collection of Retail CWLS funding, Retail CWLS is an opportunity for economic recovery after the Covid-19 pandemic, clearly the benefits, nazir certified, professional, safe and risk-free, as well as being a forum for the community to waqf money and play an important role in sustainable economic growth to support national food security. Retail Sukuk in Indonesia have been issued for the fifth time in order to strengthen the domestic economy. However, interest in retail sukuk is decreasing, especially among The Younger Generation. For future researchers, the next research should examine Retail CWLS from the perspective of investment actors and the reasons why there is minimal interest from The Younger Generation